Role of leukocytes, gender, and symptom domains in the influence of depression on hospitalization and mortality risk: Findings from the Moli-sani study - Gialluisi, Alessandro; Bracone, Francesca; Costanzo, Simona; Santonastaso, Federica; Di Castelnuovo, Augusto; Orlandi, Sabatino; Magnacca, Sara; De Curtis, Amalia; Cerletti, Chiara; Donati, Maria Benedetta; de Gaetano, Giovanni; Iacoviello, Licia (Frontiers in Psychiatry, 2022)
Background: Major Depressive Disorder is a mental illness associated with chronic conditions like cardiovascular disease (CVD). Circulating inflammation has been proposed as a potential mechanism underlying this link, although the role of specific biomarkers, gender, and symptom domains is not well elucidated. Methods: We performed multivariable Cox regressions of first hospitalization/mortality for all-cause and CVD, ischemic heart (IHD) and cerebrovascular disease (CeVD) causes vs depression severity in an Italian population cohort (N=13,191; age≥35 years; 49.3% men; 4,856 hospitalizations and 471 deaths, median follow-up 7.28 and 8.24 years, respectively). In models adjusted for age, sex and socioeconomic status, we estimated the proportion of association explained by C-reactive protein (CRP), platelet count, granulocyte-to-lymphocyte ratio (GLR) and white blood cell counts (WBC). Gender-by-depression interaction and gender-stratified analyses were performed. Associations of polychoric factors tagging somatic and cognitive symptoms were also tested with incident clinical risks, as well as the proportion explained by a composite index of circulating inflammation (INFLA-score). Results: Significant proportions of the influence of depression on clinical risks were explained by CRP (4.8% on IHD hospitalizations), GLR (11% on all-cause mortality) and WBC (24% on IHD/CeVD hospitalizations). Gender-by-depression interaction was significantly associated only with all-cause mortality (p = 0.03), with moderate depression showing a +60% increased risk in women but not in men. Stable associations of somatic but not of cognitive symptoms with increased hospitalization risk were observed (+16% for all causes, +14% for CVD causes), with INFLA-score explaining small but significant proportions of these associations (2.5% for all causes, 8.6% for IHD causes). Conclusions: These findings highlight the importance of cellular components of inflammation, gender and somatic depressive symptoms in the link between depression and clinical (especially CVD) risks, pointing to the existence of additional pathways through which depression may play a detrimental effect on cardiovascular system.